PERLINDUNGAN HUKUM USAHA MIKRO KECIL MENENGAH TERHADAP PLATFORM SOCIAL COMMERCE: Legal Protection for Micro Small Medium Enterprises Against Social Commerce Platform - Pantow, Fickry Petrus (Jurnal Globalisasi Hukum., 2024)
The rapid growth of digital businesses affects the way people conduct business transactions and switch from offline to online systems. One of the digital platforms that is experiencing rapid development in Indonesia is the Tiktok Shop social commerce platform, which has a major impact on Micro, Small and Medium Enterprises (MSMEs) business actors in Indonesia, in terms of increasing turnover and market share reach but accompanied by a number of potential legal risks that can harm MSMEs. This research to examines aspect of legal protection of MSMEs on social commerce platforms, so based on the result of this study expected to provide an understanding of legal protection for MSMEs operating in digital trade through social commerce platforms. This research using a normative method with a statutory approach that examines related and relevant regulations. The result is that the current regulations are sufficient to protect MSMEs in conducting business on social commerce platforms. However, the MSMEs must continue to adapt to technological developments along with product and service innovations in order to compete. Recommendations for regulators to consistently apply existing regulations in protecting MSMEs.